Flat Top Barge 300 feet Using Portable Dynamic Positioning System - Agoes Santoso; Juniarko Prananda; Amiadji Amiadji; Edi Jadmiko; Izzu Alfaris Murtadha (International Journal of Marine Engineering Innovation and Research, 2017)
Portable Dynamic Positioning System has not commonly applied to the ship, especially on barge. Besides for Dynamic Positioning function, the system can be used as ship's main propulsion. By using this system, the ship able to not using anchors because the functions can be performed by the Portable Dynamic System. Therefore, research about the application of Portable Dynamic Positioning System on the ship is conducted. This research aims to design a Flat Top Barge 300feet ship, to determine the specifications of Portable Dynamic Positioning System which is used, and to find out the ship stability which is designed on the empty payload condition and maximum payload. This research designed the ships with main dimensions LWL 90.1 meters, 25 meters wide, 5.5 meters high and 4.2 meters draught. To generate the ship with a maximum speed of 8 knots, it takes four thruster supplied with power 225 kW each, so that the total generated power is 1100 kW. This study analyzes three conditions of the ship stability, there are the condition of full payload, empty payload, and maximum payload. Each payload conditions will be analyzed regarding the large payload and draught water produced. The first is full payload conditions resulting payload in the amount of 5650 ton with a draught on the LCF at 4,181 meters. The second is the large empty payload condition displacement is 2809 ton and water draught on the LCF at 1,591. And the last is maximum payload conditions, resulting payload in the amount of 7450 ton with a draught on the LCF at 4,994 meters.